Chronic Periaortitis (Retroperitoneal Fibrosis) Concurrent with Recurrent Cutaneous Eosinophilic Vasculitis. (8th September 2011) - Kiorpelidou, Despoina; Gaitanis, Georgios; Zioga, Aikaterini; Tsili, Athina C.; Bassukas, Ioannis D.
Abstract : Chronic periaortitis (CP) is usually accompanied by at least mild manifestations of systemic autoimmunity; however, skin manifestations are rare. Here, we report an 82-year-old woman presenting with a pruritic annular eosinophilic dermatosis that led to the diagnosis of recurrent cutaneous eosinophilic vasculitis (RCEV) coexisting with a latent CP. The present paper is reminder that a CP should be included as a potential differential diagnosis in the elaboration of patients with cutaneous vasculitis that is suspicious of underlying autoimmunity.